Hydrothermal synthesis of MCM-41 using differently manufactured amorphous dioxosilicon sources - Gaydhankar, T. R.; Samuel, V.; Joshi, P. N. (Materials Letters, 2006)
The influence of differently manufactured amorphous dioxosilicon sources such as fumed silica (FS), spray dried precipitated silica (PSI) and flash dried precipitated silica (PS,) on the course of structural development and properties of hydrothermally prepared siliceous MCM-41 phases have been investigated. Powder XRD, N-2 adsorption/desorption and scanning electron microscopy techniques were used for sample characterization. On the basis of results obtained from time dependent study on the progressive development of MCM-41 mesophases, the reactivity trend of dioxosilicon sources observed was as: FS > PS1 > PS2. MCM-41 synthesized using least expensive PS2 having less surface area has exhibited thicker pore walls but poor orderness, while MCM-41 prepared from expensive FS having high surface area has thinner pore walls and was well ordered. The extent of contraction caused by calcination, magnitude of the wall thickness and structural stability were found to be dependent on manufacturing process of dioxosilicon sources. The noticeable morphological differences were also observed by variations in the type of dioxosilicon sources used in the hydrothermal synthesis MCM-41 materials. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Characterization; dioxosilicon sources; Hydrothermal synthesis; MCM-41; porosity; Structural stability

Hierarchical K/LTL zeolite as solid base for aqueous phase hydrogenation of xylose to xylitol - Tangale N. P.; Niphadkar, P. S.; Joshi, P. N.; Dhepe, P. L. (Microporous and Mesoporous Materials, 2019)
Post-synthesis modification by alkali treatment was employed for the synthesis of hierarchical K/LTL zeolites with varying degree of mesoporosity. For the alkali treatment, the concentration of aqueous KOH solution was changed from 0.3 to 2.8 M keeping the quantity per gram of zeolite fixed. The influence of the alkali concentration on the chemical composition, powder XRD crystallinity, morphology, basicity, and the textural properties of resultant hierarchical zeolites was investigated. Variation in the concentration of KOH solution was found to control the degree of preferential desilication with the preserved structural fingerprint of K/LTL zeolite. As a result, the generation of mesoporosity was observed along with 1) the decrease in the Si/Al ratio and percentage relative crystallinity, and 2) an increase in BET surface area and mesopore volume. 27Al MAS-NMR results showed that all the aluminum atoms present in the tetrahedral coordination after alkali treatment, which provides an elegant approach for significantly increasing the basic sites in the hierarchical zeolites. As a heterogeneous catalyst, the hierarchical K/LTL zeolites demonstrated the improved performance in the hydrogenation of xylose to xylitol as compared to the parent K/LTL zeolite. The different process parameters were assessed in order to maximize the hydrogenation activity. Among all the hierarchical zeolites, the enhanced catalytic activity was shown by the hierarchical K/LTL prepared by using 1.5 M KOH solution when it is used along with the 3.5 wt% platinum loaded γ-Al2O3 catalyst. This optimum activity may be attributed to the higher surface area, accessible basic sites, nano-sized Pt on γ-Al2O3, and the development of substantial intracrystalline mesoporosity for the enhanced molecular diffusion of reactant to and from the hierarchical zeolite with better-preserved crystallinity.